2013
DOI: 10.1097/mco.0b013e328361dc70
|View full text |Cite
|
Sign up to set email alerts
|

Cancer control and prevention

Abstract: Natural foods and bioactive food components have characteristics and functions that are similar to epigenetic inhibitors and therefore have potential in cancer control and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 120 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Investigate the factors that relate to carcinogenesis may contribute to strategies for cancer treatment and prevention [ 25 ]. As epigenetic aberrations occur and initiate events in tumorigenic processes, epigenetic treatment is a promising strategy for cancer prevention [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigate the factors that relate to carcinogenesis may contribute to strategies for cancer treatment and prevention [ 25 ]. As epigenetic aberrations occur and initiate events in tumorigenic processes, epigenetic treatment is a promising strategy for cancer prevention [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence indicates that cancer can occur without a change in the nucleotide sequence, through so-called epigenetic alterations. In fact, a combinational crosstalk between genetic and epigenetic alterations has been observed in cancer development, progression, and recurrence [ 32 ]. Both gene mutations and epigenetic alterations can be caused by exposure to various environmental factors, such as dietary components, smoke, and chemicals.…”
Section: Epigenetics and Cancermentioning
confidence: 99%
“…Epigenetic dysregulation, such as increased activity of histone deacetyltransferases (HDACs) and DNA methyltransferases (DNMTs) and changes in noncoding RNA expression, may lead to alterations in the transcription and expression of genes involved in the regulation of cell proliferation and differentiation, cell cycle, and apoptosis [ 32 37 ]. The present studies indicated that the level of HDAC5 expression was increased in human glioma and hepatocellular carcinoma, which promoted the proliferation of tumor cells via upregulating Six 1 (Sineoculis homeobox homolog 1) and Notch 1, respectively [ 38 , 39 ].…”
Section: Epigenetics and Cancermentioning
confidence: 99%
“…As we all known, diet is a major aspect of the environment may influence DNA methylation [ 13 ] and especially interesting are nutrients, which are needed for nucleic acid and DNA synthesis and for the enzymes regulating their syntheses, for example, essential amino acids, zinc, vitamins, and so on [ 14 , 15 ]. One of most strongly implicated nutrients is folate, which is a generic term for a naturally occurring family of B-group vitamins composed of an aromatic pteridine ring linked to p-aminobenzoic acid and a glutamate residue B-6 and B-12 [ 3 , 16 ].…”
Section: Introductionmentioning
confidence: 99%